THE ARTISTIC EXPRESSION OF THE FEMALE PSYCHE IN ISAJON SULTAN'S NOVEL "ALISHER NAVOI" - Charos Ravshan qizi, Shomurotova (Journal of Higher Education and Academic Advancement, 2025)
Objective: This study aims to explore the artistic expression of the female psyche in Isajon Sultan's novel "Alisher Navoi," focusing on the portrayal of historical and fictional female characters within the socio-cultural and political context of the Timurid era. Method: Utilizing a qualitative literary analysis approach, the research examines the narrative techniques, character development, and psychological portrayal employed by the author to depict female characters, such as Qutbiya, Gavharshodbegim, and Khadijah Begum. Results: The analysis reveals that Sultan effectively integrates historical authenticity with artistic imagination to highlight women's roles in historical processes, emphasizing their emotional depth, socio-political influence, and maternal instincts. The nuanced depiction of their inner worlds not only enriches the narrative but also challenges traditional literary stereotypes by presenting women as complex, multidimensional figures. Novelty: This study contributes to Uzbek literary criticism by offering a comprehensive interpretation of female representation in historical fiction, illustrating how Sultan's work transcends conventional gender portrayals through a blend of historical realism and psychological insight.